Invented traditions and creation of belonging space: A literature review (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
The present study aimed to present the initial ideas being developed in a research carried out in the scope of the PhD in Performing Arts at UNB. The research aimed to expose the conceptions of the Festa dos Bonecos Gigantes, which take place in the municipality of Taquaruçu, in Tocantins, to defend the hypothesis that it constitutes an invented tradition, which was designed in order to designate a space of belonging hitherto non-existent for its makers. Here, concepts from different fields of knowledge were discussed to first support the concept of belonging as an ontological institution inherent to human beings in society. Afterwards, the concept of invented traditions was discussed, and finally, the research locus and the affectation of this work were presented: the aforementioned party. It is possible to understand the Aldeia TabokaGrande as a space invented to feel belonging.
Keywords: Tradition; Taquaruçu; Giants Puppets